Two new species of eriophyid mites (Acari: Eriophyidae) from Guadeloupe and Marie Galante, with records on other plant mites - Flechtmann, Carlos H.w.; Etienne, Jean (Zootaxa, 2003)
Four species of phytophagous mites are reported from Guadeloupe and Marie Galante: a spider mite, Tetranychus gloveri Banks, one eriophyid mite, Acalitus maracai (Boczek & Nuzzaci) and two new species of Eriophyidae, namely Acalitus macrosetosus n. sp. from Dalbergia ecastaphyllum (Fabaceae) and Aceria geniculatus n. sp. from Inga laurina (Mimosaceae).